Approaches to Defining and Measuring Russia’s Internet Economy - Sergey Plaksin; Gulnara Abdrakhmanova; Galina Kovaleva (Foresight and STI Governance)
The rapid development of digital technologies is changing production processes and forms of interaction. It has encouraged growing interest in electronic content and created a new segment of the economy where all actors rely on the internet. These processes are most noticeable in developed countries. Russia is no exception. The development of the domestic segment of the internet economy — the economy of the Runet — is of particular importance due to the size of the country, the significant socioeconomic heterogeneity and underdevelopment of the transportation networks in the Russian regions. A study of the phenomenon of the internet economy requires a reliable information base. It is hard to provide an adequate quantitative estimate of the size of the Internet economy for the following reasons. First, the existing statistical indicator system was created before the Internet and Internet businesses were widespread. Secondly, this new segment of economy is much more heterogeneous than traditional sectors and industries and thus difficult to measure.